Inner Conflict and Personality Structure of the Characters in the Film 1 kakak 7 keponakan: A Psychoanalytic Study of Sigmund Freud - Niken Naodia Darti; Siti Nur Afifatul Hikmah (Universitas Islam Negeri Palopo, 2026)
This study examines the inner conflicts and personality structures of the central characters in the film 1 Kakak 7 Keponakan. This study uses a qualitative descriptive method with a literary psychology approach based on Sigmund Freud's psychoanalytic theory, particularly the concepts of id, ego, and superego. Data collection techniques are carried out through observation and note-taking techniques on dialogues, scenes, and the actions of the characters shown in the film. The purpose of this study is to describe the forms of inner conflicts and analyze the personality structures of the characters in facing the pressure of family responsibilities and social demands. The results of this study indicate that the characters in the film 1 Kakak 7 Keponakan experience inner conflict stemming from the conflict between personal desires, moral demands, and family obligations. The ego and superego personality structures appear more dominant in most characters, which is reflected through rational attitudes, empathy, and self-sacrifice in facing the realities of life. This inner conflict is controlled by the dynamics of interaction between the id, ego, and superego which influence the decisions and actions of the characters throughout the storyline.